S1 Guideline: Diagnosis and therapy of vitiligo. (4th March 2022) - Böhm, Markus; Schunter, Jo Ana; Fritz, Klaus; Salavastru, Carmen; Dargatz, Sonja; Augustin, Matthias; Tanew, Adrian
Summary: Vitiligo is a common skin disorder characterized by immune‐mediated destruction of melanocytes. Non‐segmental vitiligo, the most common clinical subtype, has usually a chronic course and often results in significant psychosocial consequences for the affected patient. Early recognition, awareness of comorbidity, precise assessment of disease extent and activity, evaluation of impairment of quality of life as well as rapid initiation of treatment based on currently available evidence‐based therapies are crucial cornerstones in the management of vitiligo. This S1 guideline helps German dermatologists to better diagnose and treat vitiligo.